Implementation of the Andragogy Learning Model in Andragogy Competency Training for PKBM Tutors - Yuka Martlisda Anwika; Titi Maemunaty; Wilson Wilson; Aswandi Bahar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This study aims to determine the implementation of the Andragogy Learning Model in Andragogy Competency Training for PKBM Tutors in Kampar Regency. The method used is descriptive qualitative. Researchers used observation, interviews and documentation. Sources of data are 2 tutors 5 students. The results showed that the implementation of the andragogy learning model was the delivery of material from the tutor/training instructor according to the material that had been mutually agreed upon, then there was a question and answer or discussion for joint evaluation. The results of the andragogy learning model showed that there was an increase and change in terms of knowledge, attitudes and skills. In knowledge knowing about andragogy competencies and how to apply them in adult learning. In attitude that the trainees are very good in attitude, behavior and activity so that enthusiasm in learning is very good. In terms of skills, participants have been able to practice in learning about andragogy competencies because they have in-depth understanding of andragogy competencies for tutors after training. The supporting factors are the enthusiasm of the participants, the focus of the participants, supported by PKBM Mutiara Kampar, the network between PKBM and tutors who are able to guide the participants well, and teach the material as expected. The inhibiting factor is the timing and delivery of materials that adapt to the understanding of the participants.